Strategi Pengembangan Kain Tenun Sabu Raijua Sebagai Produk Unggulan Khas Nusa Tenggara Timur - Rinny, Rinny (Peneliti.net, 2024)
The aim of this study was to determine the effect of motivation on tourists' visiting decisions on Onrust Island, to determine the effect of perceptions on tourists' visiting decisions on Onrust Island, and to determine the effect of motivation and perceptions on tourists' visiting decisions on Onrust Island. The results of the study show that both simultaneously and partially, motivational variables (X1) and perceptions (X2) have a significant positive effect on the decision to visit (Y). And based on the results of the determination, the R2 value is 0.683, which means that motivation and perception influence the decision to visit by 68.3%